Nanofibrous Composite with Tailorable Electrical and Mechanical Properties for Cardiac Tissue Engineering. (15th December 2019) - Roshanbinfar, Kaveh; Vogt, Lena; Ruther, Florian; Roether, Judith A.; Boccaccini, Aldo R.; Engel, Felix B.
Abstract: Cardiac tissue engineering is a promising strategy to prevent functional deterioration or even to enhance cardiac function upon myocardial infarction. Here, electrospun fiber mats containing different combinations of electrically conductive polyaniline, collagen, and/or hyaluronic acid are assessed regarding material properties and compatibility with cardiomyocyte attachment and function. Microstructure analysis reveals that collagen fiber mats contain a wide range of fiber diameters after crosslinking (from ≈300 nm to ≈5 µm); all other fiber mats contain fibers in the range of ≈120 to ≈300 nm. Fiber mats exhibit comparable electrical conductivity to and greater mechanical properties than the native human myocardium, which is considered beneficial. Cell–matrix interaction analysis utilizing postnatal rat cardiomyocytes reveals that the fiber mats are non‐cytotoxic and permit cell attachment and contraction. Fiber mats containing collagen (9.89%), hyaluronic acid (1.1%), and polyaniline (PANi, 1.34%) exhibit the most favorable properties with longer contraction time, higher contractile amplitude, and lower beating rates. Improved contraction is accompanied by increased connexin 43 expression. Importantly, this fiber mat is a suitable material for human‐induced pluripotent stem cell–derived cardiomyocytes regarding cytotoxicity, cell attachment, and function. Collectively, these data demonstrate that fiber mats made of collagen, hyaluronic acid, and polyaniline are promising materials for cardiac tissue engineering. Abstract : Facilitating intercellular electrical communication in tissue engineering is challenging. Here, electroconductive fibrous scaffolds with tailorable mechanical and electrical properties are presented. Cardiomyocytes show improved contractile amplitude, intercellular junctions, and higher beating rates.